Heritability of abnormalities in limbic networks of autism spectrum disorder children: Evidence from an autism spectrum disorder twin study. Issue 4 (24th February 2022) - Fu, Linyan; Li, Chunyan; Li, Yun; Cheng, Xin; Cui, Xiwen; Jiang, Jiying; Ding, Ning; Fang, Hui; Tang, Tianyu; Ke, Xiaoyan
Abstract: Although the limbic system is closely related to emotion and social behaviors, little is known about the integrity of limbic pathways and how genetics influence the anatomical abnormalities of limbic networks in children with autism spectrum disorder (ASD). Therefore, we used an ASD twin study design to evaluate the microstructural integrity and autism‐related differences in limbic pathways of young children with ASD and to estimate the heritability of limbic tracts microstructure variance. We obtained diffusion tensor imaging scans from 33 pairs of twins with ASD aged 2–9 years and 20 age‐matched typically developing children. The ACE model was used to estimate the relative effects of additive genetic factors (A), shared environmental factors (C) and specific environmental factors (E) on the variability of diffusivity measurements. We found a significant decrease in fractional anisotropy (FA) in the bilateral fornix and uncinate fasciculus (UF), as well as increased mean diffusivity (MD) and radial diffusivity (RD) in the bilateral fornix and right UF of ASD children. Correlation analysis showed that FA, MD, and lateralization indices of UF were correlated with autism diagnostic observation schedule scores. The ACE model revealed that genetic effects may drive some of the variability of microstructure in the bilateral fornix, cingulum, and left UF. In conclusion, in children with ASD, there are abnormalities in the white matter microstructure of the limbic system, which is related to the core symptoms; these abnormalities may be related to the relative contribution of genetic and environmental effects on specific tracts. Lay Summary: Autism spectrum disorder (ASD) children have abnormal white matter structure in limbic system related to ASD symptoms, and genetic factors play an important role in the development of limbic tracts.